Water, Crime and Security in the Twenty-First Century Too Dirty, Too Little, Too Much - Brisman, Avi (Critical Criminological Perspectives, 2018)
Water, Crime and Security in the Twenty-First Century represents criminology's first book-length contribution to the study of water and water-related crimes, harms and security. The chapters cover topics such as: water pollution, access to fresh water in the Global North and Global South, water and climate change, the commodification of water and privatization, water security and pacification, and activism and resistance surrounding issues of access and pollution. With examples ranging from Rio de Janeiro to Flint, Michigan to the Thames River, this original study offers a comprehensive criminological overview of the contemporary and historical relationship between water and crime. Coinciding with the International Decade for Action, "Water for Sustainable Development," 2018-2028, this timely volume will be of particular relevance to students and scholars of green criminology, as well as those interested in critical geography, environmental anthropology, environmental sociology, political ecology, and the study of corporate crime and state crime.